Experimental Analysis of MISHEMT Multiple Conductions from 200K to 450K - Perina, Welder F.; Martino, Joao A.; Agopian, Paula G. D. [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2022)
In this work, the multiple conductions of a GaN based Metal-Insulator-Semiconductor High Electron Mobility Transistor (MISHEMT) when operating in a temperature range from 200K to 450K are evaluated experimentally. It is observed that the threshold voltage decreases linearly with temperature from 200K to room temperature. For higher temperatures, there is a competition among the following effects: the bandgap narrowing, depletion depth and Fermi potential reductions, resulting in the increase of threshold voltage. The analysis of the subthreshold swing presents very high values indicating a harsh degradation. These behaviors are further investigated through the MISHEMT transconductance, which presents two different conduction mechanism (double peak) at 350 K for all channel lengths, affecting the total drain current.
Keywords: basic parameters; GaN; heterostructure; MISHEMT; temperature